Correlations between fracture width and Reynolds number of 3-D single fractures. Issue 3 (October 2021) - Wang, X; Liu, R; Yu, L
Abstract: This study shows a numerical simulation on the relationship between fracture width ( W ) and the Reynolds number ( Re ) for fractures having different joint roughness coefficients (JRCs). Numerical simulations by solving the Navier-Stokes (NS) equations are performed to model fluid flow through single fractures. The results show that the Re of the theoretical solutions of smooth models agrees well with those of numerical simulation results, indicating that the numerical code is reliable. As W increases from 5 mm to 200 mm, the Re increases significantly and then slightly. When the W is large, the change in Re gradually becomes smaller. This indicates that there is a critical W ( W C ), in which the influence of W on the Re is negligible when W exceeds the W C . When JRC is 0, 5.84 and 19.20, the corresponding W C is 27.38 mm, 26.55 mm and 24.63 mm, respectively.